Data on expression of genes involved in estrogen and progesterone action, inflammation and differentiation according to demographic, histopathological and clinical characteristics of endometrial cancer patients - Sinreih, Maša (Data Brief, 2017)
Endometrial cancer is the sixth most common cancer in women worldwide. It is associated with aberrant actions of steroid hormones, estrogens and progesterone, but also with enhanced inflammation and reduced cellular differentiation. Here, we show data on demographic and histopathological characteristics of 51 patients with endometrial cancer, together with data on correlations between the expression of 38 genes involved in estrogen and progesterone actions, inflammation and differentiation, and demographic characteristics. We also show data on changes in gene expression of these 38 genes according to histopathological and clinical characteristics of these patients. This article includes data referenced in the manuscript entitled »STAR and AKR1B10 are down-regulated in high-grade endometrial cancer by Sinreih et al. (in press) [1].